Localization of the therapeutic targets for endothelin receptor antagonists and sodium-glucose co-transporter 2 inhibitors in the chronic liver disease, primary sclerosing cholangitis - Kuc, Rhoda E.; Paterson, Anna L.; Williams, Thomas L.; Gelson, William T. H.; Greasley, Peter J.; Ambery, Phil; Maguire, Janet J.; Davenport, Anthony P. (Frontiers in Pharmacology, 2025)
IntroductionPrimary sclerosing cholangitis (PSC) is a chronic liver disease of unknown cause contributing to cirrhosis and cancer but has no cure. PSC is characterized by inflammation within ductal fibrosis, progressive bile duct narrowing and loss, with damage to cholangiocytes (epithelial cells affecting bile production) and liver repair. ET-1, produced by cholangiocytes, contributes to fibrosis, vasoconstriction, and inflammation via ETA receptors. In patients, ET-1 and ETA gene expression are elevated and ETA antagonists reduce disease progression in PSC animal models. Ongoing clinical trials of portal hypertension in liver disease are testing the efficacy of a new treatment strategy combining ETA-selective antagonist zibotentan with SGLT2 inhibitor dapagliflozin.MethodsTo interrogate the potential of a comparable strategy in PSC we have initially compared the localization of ET receptors and SGLT2 transporter in human PSC liver.ResultsIn ethically sourced healthy human liver, ETA immunofluorescence was primarily found in bile duct epithelial cells within the portal tract, smooth muscle of the central vein, with low levels in hepatocytes. SGLT2 immunofluorescence was mainly detected on bile duct epithelial cells and hepatocytes. ETA co-localized with smooth muscle cells in large arteries and veins, while ETB immunoreactivity was present in hepatocytes and endothelial cells. In the PSC vasculature, the pattern of expression of smooth muscle ETA receptors that mediate vasoconstriction was retained, consistent with the hypothesis that ETA selective antagonists would be beneficial in reducing portal hypertension. ETB receptors were principally localised on endothelial cells and would be expected to mediate beneficial vasodilation. In diseased areas, all three proteins localised to ductal reactions, reflecting the response of the liver to injury, involving cholangiocyte proliferation, promoting beneficial regeneration but also associated with fibrosis and inflammation. Both ETA, ETB and low levels of SGLT2 immunofluorescence localised to fibroblasts within the fibrous septa where bands of scar tissue can restrict hepatic blood flow, leading to cirrhosis.DiscussionBoth drug targets were retained in the key hallmarks of PSC pathology; ETA and SGLT2 staining within cholangiocytes undergoing ductal transformation and cells within the fibrotic septa, supporting the proposed benefit of combination treatment strategy.